The Construction of a Portfolio Using Varying Methods and the Effects of Variables on Portfolio Return - Manurung, Adler Haymans; Machdar, Nera Marinda; Sijabat, Jadongan; Manurung, Amran (International Journal of Economics and Financial Issues, 2024)
This research aims to explore for portfolio construction using vary method which is Markowitz, Elton Gruber, Equal Weighted, Market Cap, and Safety-First Criterion (Roy and Kataoka Criterion). Data was used monthly data of Kompas 100 Index for period of 2015 to June 2023. The result found that 53 stocks for using Elton Gruber, Equal weighted, market capitalization, Markowitz Method. There is no difference average return for portfolio of Elton Gruber, Equal weighted, market capitalization, Markowitz Method, The research’s findings are as follows Roy and Kataoka as representative Safety-first criterion could be used to construct portfolio with determining achievement of minimum return of 0.797% per month with risk premium of 0.2% . Portfolio return using Roy criterion is vary from 3.973% to 13.397% per month and Kataoka criterion has return vary from 8.861% to 15.48% for equal weighted. Then the equal weighted portfolio return is highest than market capitalization weighted Portfolio return. Elton Gruber method also used to construct portfolio, then this method has highest cumulative return compared to others methods. The Market shock affected all portfolio return and Interest rate has affected portfolio return for equal weighted and Elton Gruber Method. Pandemic Era affect portfolio return for Market Capitalization Weighted portfolio.